DINAMIKA PERKAWINAN DI BAWAH UMUR DI ERA DIGITAL - Putri Maha Dewi; Desi Syamsiah; Karmina Siska (LPSDI Bina Patria, 2023)
Marriage is the union of two families that is legalized by society, law and religion. Provisions regarding marriage have been regulated in Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 which is referred to as the Marriage Law. The Marriage Law stipulates that the minimum age limit for the two prospective brides to be able to marry is 19 (nineteen) years. If in the implementation of marriage, one or both of them is not yet 19 years old, then the event is referred to as underage marriage. The occurrence of this phenomenon is motivated by various things, one of which is digital technology. If there is a deviation from the provisions of the time limit, the marriage may be carried out on condition that it obtains permission from the court in advance. This study aims to determine how the dynamics of underage marriage in the digital era. This paper uses a normative legal research method that examines secondary data. The results of this study indicate that in this digital era the number of underage marriages has increased significantly, especially during the COVID-19 pandemic which requires educational activities to be carried out online. This can be seen from the request for a marriage dispensation submitted to the court which occurred during the COVID-19 pandemic.